A case of hypoglossal nerve palsy with evolving cranial nerve involvement in renal cell carcinoma: a case report - Shadi Shams; Abigail Broughton; Katrina Lambeth; Aditi Trivedi; Dehua Wang; Sun Choo; Katherine Dove (Journal of Medical Case Reports)
Abstract Background Renal cell carcinoma is a rare pediatric solid tumor that typically presents with hematuria, abdominal mass, or flank pain. It is uncommon for renal cell carcinoma to manifest with headache and isolated extra-urogenital symptoms. We present, to our knowledge, the first case of renal cell carcinoma with bony metastases, presenting initially as isolated cranial nerve twelve palsy. Although bony metastases can occur in renal cell carcinoma, skull-based metastases and cranial neuropathies are exceedingly rare, especially in the pediatric population. Case presentation We describe the unusual presentation of renal cell carcinoma with bony skull-based metastases presenting initially as isolated hypoglossal nerve palsy, that progressed to multiple cranial neuropathies in a previously healthy 14-year-old female of Indian descent. Conclusion The differential for hypoglossal nerve with evolving cranial nerves 9 and 10 involvement can be broad owing to the course of the nerve, the structures surrounding it, and its pathway. It is important for providers to include bony metastatic disease in the differential diagnosis for headaches with multiple cranial neuropathies.